ANALISIS KESALAHAN SISWA PADA KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN YANG MENGGUNAKAN PENDEKATAN SAINTIFIK - Dea Tri Septiani; Ari Septian; Erwan Setiawan (Department of Mathematics Education, Universitas Kuningan, 2020)
The purpose of this study is to determine the level of mathematical communication ability of students in learning that uses a scientific approach, find out the mistakes that are often made by students and which are the causes of students making mistakes. The subjects in this study were students of class XI MIPA 3 MAN 1 Cianjur. This research method is descriptive qualitative and the instruments used consist of tests of mathematical communication ability and interviews. The results of this study are students' mathematical communication ability in explaining ideas, situations, and mathematical relationships in writing with real objects, pictures, graphics and algebra by 34%. Mathematical communication ability of students in explaining ideas, situations, and mathematical relationships in writing with real objects, pictures, graphics and algebra by 25%. The ability of students' mathematical communication in expressing everyday events in language or mathematical symbols or composing a mathematical model of an event is 30%. Mistakes that are often made by students in this study are concept errors, operating errors, and lack of accuracy. As for what causes students to make mistakes is due to factors of forgetfulness, lack of accuracy, difficulty in learning and less study time at home.